Intersegmental vessel formation in zebrafish: requirement for VEGF but not BMP signalling revealed by selective and non-selective BMP antagonists - Cannon, JE (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: Bone morphogenetic proteins (BMPs) were first identified through their role in inducing bone and cartilage formation, but many other important functions have since been ascribed to BMPs, including dorsoventral patterning, angiogenesis and tissue homeostasis. Using dorsomorphin and LDN193189, selective small molecule inhibitors of BMP signalling, we investigated the role of BMP signalling in early vascular patterning in zebrafish. EXPERIMENTAL APPROACH: The effects of dorsomorphin and LDN193189 on vascular endothelial growth factor-a (VEGF) and BMP signalling in developing zebrafish and in human pulmonary artery endothelial cells were determined using confocal microscopy, Western blotting and quantitative PCR. KEY RESULTS: We showed that dorsomorphin, similar to the VEGF inhibitor SU5416, strongly inhibits intersegmental vessel formation in zebrafish and that this is due to inhibition of VEGF activation of VEGF receptor 2 (VEGFR2), leading to reduced VEGF-induced phospho-ERK (extracellular regulated kinase) 1/2 and VEGF target gene transcription. These effects occurred at concentrations of dorsomorphin that block BMP signalling. We also showed that LDN193189, an analogue of dorsomorphin, more potently blocks BMP signalling but has no effect on VEGF signalling in zebrafish and does not disrupt early vascular patterning. CONCLUSIONS AND IMPLICATIONS: Dorsomorphin inhibits both BMP and VEGF signalling, whereas LDN193189 is a more selective BMP antagonist. Results obtained in cardiovascular studies using dorsomorphin need to be interpreted with caution, and use of LDN193189 would be preferable due to its selectivity. Our data also suggest that BMP signalling is dispensable for early patterning of intersegmental vessels in zebrafish.